EVALUASI PELAKSANAAN PENILAIAN KELAS PADA MATA PELAJARAN PRODUKTIF ADMINISTRASI PERKANTORAN DI SMK BHAKTI PERSADA KABUPATEN KENDAL - Suryani, Nanik; Pramusinto, Hengky (Dinamika Pendidikan, 2011)
The objective of this study is to evaluate the class assessment from many aspects; aspect and technique of class assessment, procedure of class assessment, they way to determine the studentsâ score rank, and the opinions of teachers, the principal, students about the practice of class assessment. The research is an evaluation research with a formative model. The subjects of this study were 3 teachers, 1 principal and 146 students of Office administration department. The data were collected with questionnaire, documentation and interview. The result showed that (1) aspect and technique of class assessment conducted by the teacher, based on studentsâ opinion was on poor category, based on the teachersâ opinion was on good category and based on the principalâs opinion was on very good category. Therefore, it was on good category, (2) assessment aspects conducted by the teachers were only cognitive and psychometric aspects; while affective aspect has not conducted yet. Thus, it was not comprehensive assessment, (3)the techniques of assessment used by the teachers were written test, oral test, practice, observation and task, however, portfolio assessment, journal, self-assessment and peer- assessment have not conducted yet in this subject, (4) the procedure of assessment based on students was poor, meanwhile the teachers and principal said it was good. (5) procedure of assessment conducted by the teachers did not fulfill the standard as stated in Panduan Penilaian Mata Pelajaran Produktif (The Assessment Guidance of Productive Subject) by Badan Standar Nasional Pendidikan (BSNP), (6) determining studentsâ end score is by combining studentsâ daily test, mid test, midterm test and final test and then divided into three, while all tasks are only the supporting score, and (7) the principal, the teachers and students expect the class assessment in still conducted since it gives benefit and improve studentsâ development significantly in education world.